The nusantara ethnic groups from historical and genomic perspectives - Engku Ahmad Zaki, Engku Alwi; Norazmi, Anas; Zuriani, Yaacob (IAEME Publication, 2019)
Malays are a distinctive nation native as well as among the oldest ethnic group in the world encompassing the land of Nusantara, Madagascar and the Pacific Islands. The Malay civilization is associated with the Southeast Asian region known as the Malay Archipelago, the Malay-Indonesian Archipelago, the Nusantara, the Malay Realm and the Land of Java. It also includes the islands of Indonesia, Malaya, the islands of Borneo, Philippines, Singapore which consisting two communities namely Proto-Malay (aboriginal Malay) and Deutero-Malay (new Malay). Therefore, this study attempts to shed some light on the origins of the Malay community from the historical point of view and its relation to modern genomic field. The findings indicate that there is a significant relationship between the history of Malay origins and the modern genomic field that was done through the mitochondrial DNA analysis. This is followed by the Nusantara that serves as the major genetic reservoir of the world Malay group. Thus, it is apparent that the genomic study of the Malay ethnic group is not solely focused on the origins of the nation alone, but to enhance the health level of the race through disease analyses, medical practice and research. Subsequently, this will lead to the production of pharmaceutical products which is indeed beneficial in addressing local health needs.